Using an interprofessional competency framework to examine collaborative practice. Issue 2 (March 2015) - Hepp, Shelanne L.; Suter, Esther; Jackson, Karen; Deutschlander, Siegrid; Makwarimba, Edward; Jennings, Jake; Birmingham, Lisa
Abstract Healthcare organisations are starting to implement collaborative practice to increase the quality of patient care. However, operationalising and measuring progress towards collaborative practice has proven to be difficult. Various interprofessional competency frameworks have been developed that outline essential collaborative practice competencies for healthcare providers. If these competencies were enacted to their fullest, collaborative practice would be at its best. This article examines collaborative practice in six acute care units across Alberta using the Canadian Interprofessional Health Collaborative (CIHC) competency framework (CIHC, 2010). The framework entails the six competencies of patient-centred care, communication, role clarification, conflict resolution, team functioning and collaborative leadership (CIHC, 2010). We conducted a secondary analysis of interviews with 113 healthcare providers from different professions, which were conducted as part of a quality improvement study. We found positive examples of communication and patient-centred care supported by unit structures and processes (e.g. rapid rounds and collaborative plan of care). Some gaps in collaborative practice were found for role clarification and collaborative leadership. Conflict resolution and team functioning were not well operationalised on these units. Strategies are presented to enhance each competency domain in order to fully enact collaborative practice. Using the CIHC competency framework to examine collaborative practice was useful for identifying strength and areas needing improvement.